The Influence of Service Quality, Perceived Value, Satisfaction, and Trust towards Loyalty in Universities - Changwen, Li; Vongchavalitkul, Busaya; Navavongsathian, Ampol (Rajapark Journal, 2025)
This article investigated the influence of service quality, perceived value, satisfaction, and trust towards loyalty in universities. Adopting a quantitative research methodology, the study surveyed 850 university students, yielding 708 valid responses. The analysis was conducted using SPSS 26.0 and Structural Equation Modeling (SEM) to rigorously test the hypotheses on service quality, perceived value, student satisfaction, trust, and their collective impact on loyalty. The findings revealed that while service quality did not directly affect satisfaction, perceived value significantly influences both satisfaction and confidence, which augments loyalty. This study contributed to the literature by highlighting the mediating role of perceived value in the service quality-loyalty nexus and the importance of trust in fostering long-term relationships between students and universities. The research outcomes offered strategic recommendations for higher education institutions to enhance student loyalty. It suggests that universities should improve service quality and perceived value to bolster student satisfaction and trust. Additionally, the study underscored the importance of leveraging technology to enhance educational services and engagement, fostering a culture that values student feedback, and building strong alum networks to sustain loyalty post-graduation. These insights provide actionable guidance for university administrators to craft strategies that can enhance student loyalty and ensure their institutions' long-term success in the competitive landscape of higher education.